2015
DOI: 10.1038/srep14539
|View full text |Cite
|
Sign up to set email alerts
|

Novel nano bearings constructed by physical adsorption

Abstract: The paper proposes a novel nano bearing formed by the physical adsorption of the confined fluid to the solid wall. The bearing is formed between two parallel smooth solid plane walls sliding against one another, where conventional hydrodynamic lubrication theory predicted no lubricating effect. In this bearing, the stationary solid wall is divided into two subzones which respectively have different interaction strengths with the lubricating fluid. It leads to different physical adsorption and slip properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…It was shown that the relative slip amount is constant in the inlet zone of the channel, where the interfacial slippage occurs. This substantiates the assumption made in the analysis of this kind of channel as shown in the study by Zhang (2015). It was also shown that with the increases of the channel height or the fluidwall interfacial shear strength, the interfacial slippage is reduced.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…It was shown that the relative slip amount is constant in the inlet zone of the channel, where the interfacial slippage occurs. This substantiates the assumption made in the analysis of this kind of channel as shown in the study by Zhang (2015). It was also shown that with the increases of the channel height or the fluidwall interfacial shear strength, the interfacial slippage is reduced.…”
supporting
confidence: 88%
“…In the study by Zhang (2015), an analysis was presented for a nano bearing formed between two parallel smooth solid planes respectively considering the fluid-wall interfaical slippage in the bearing inlet and outlet zones, by using the parameter of the relative slip amount ( s  ). In that analysis (Zhang, 2015), it was assumed that the relative slip amounts were respectively constant in the bearing inlet and outlet zones, and it was also phrased that the relative slip amount should be dependent on the fluid-wall interfacial shear strength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Plots of f w against φ tot for given ψ φ values (Zhang, 2015a) When φ tot = 2π, the dimensionless load is:…”
Section: Carried Load and Attitude Angle Of The Bearingmentioning
confidence: 99%